Effect of storage conditions on phytochemical characteristics and activities of black tea cultivated from geographically different landscapes - Syed Ali Raza Naqvi; Sumaira Naz; Muhammad Irfan; Ameer Fawad Zahoor; Atif Hussain Randhawa; João Miguel Rocha; Mohamed Fawzy Ramadan (South African Journal of Botany, 2026)

Discovery and Functional Evaluation of Enterobacter gossypi sp. nov. (RT) for Salinity Stress Alleviation in Cotton - Abid Ullah; Aqsa Bibi; Ma Yonghui; Muhammad Atif Azeem; Ali Hazrat; Yasir Arafat; Caixia Han; Nigora Kuchkarova; Hua Shao (Journal of Soil Science and Plant Nutrition, 2026)

Pharmaco-therapeutic modulation of the Glo1–Nrf2–RAGE functional network in chronic inflammation: polyphenols in the context of current anti-inflammatory therapy - Sajid Ali; Muhammad Saeed Akhtar; Adnan Amin; Atif Ali Khan Khalil; Wajid Zaman (Inflammopharmacology, 2026)

Green-Synthesized Gold Nanoparticles from Fortunella Margarita (Kumquat) Leaf Extract for Broad-Spectrum Antifungal Control of Postharvest Fruit Crop Pathogens - Bismillah Mubeen; Ammarah Hasnain; Haider Ali; Muhammad Nadeem Khan; Maymoona Saher; Muhammad Umer Iqbal; Syed Atif Hasan Naqvi (Applied Fruit Science, 2026)

Light and temperature differentially influence morphology, phytohormone profiles, and phenolic acid biosynthesis in Allium sativum across developmental stages - Muhammad Jawaad Atif; Bakht Amin; Muhammad Imran Ghani; Muhammad Ali; Zhihui Cheng (Biologia, 2026)

Enhancing Soil and Atmospheric Carbon Regulation Through Bombax Ceiba-Based Agroforestry in Drylands - Ghulam Yasin; Muhammad Talha Bin Yousaf; Muhammad Atif Latif; Muhammad Azeem Sabir; Muhammad Azeem Akhter; Shafeeq Ur Rahman; Sajad Ali; Khairiah Mubarak Alwutayd; Rashid Iqbal (Water, Air, & Soil Pollution, 2026)

A comprehensive review of the phytochemical, and pharmacological potential of Alnus hirsuta (Spach) Rupr., (Siberian Alder): implications for anti-inflammatory therapeutics - Sajid Ali; Adnan Amin; Muhammad Saeed Akhtar; Khizar Abdullah Khan; Ishaq N. Khan; Imran Khan; Wajid Zaman; Atif Ali Khan Khalil (Inflammopharmacology, 2026)

Rethinking lice management at the human–animal interface: challenges, green alternatives, and the road ahead - Rimsha Jamil; Muhammad Imran; Muhammad Adnan Sabir Mughal; Rao Zahid Abbas; Muhammad Umar Ijaz; Muhammad Kasib Khan; Asghar Abbas; Farhan Ahmad Atif; Sultan Ali (International Journal of Tropical Insect Science, 2026)

Redundancy‐Resilient Multi‐Criteria Multi‐Model Ensemble Framework for Drought Assessment Under Climate Change - Hussnain Abbas; Muhammad Shakeel; Zulfiqar Ali; Rizwan Niaz; Naim Ahmad; Ali Atif Yassin Ali (International Journal of Climatology, 2026)
Reliable assessment of drought risks under climate change requires robust evaluation of climate models, redundancy‐resilient ensemble construction, and accurate quantification of extremes. Existing approaches often fail to account for non‐linear dependencies, inter‐model redundancy, and spatial performance, limiting the reliability of drought projections. This study introduces Integrated Information‐theoretic redundancy‐resilient ensemble and drought assessment (IIREDA), a multi‐criteria framework that integrates information‐theoretic dependence measures, redundancy adjustment, spatial performance consistency, and advanced ensemble techniques. Applying IIREDA to 22 CMIP6 global climate models (GCMs) across 29 grid stations in drought‐prone Balochistan (1950–2014; projected SSP1–2.6, SSP2–4.5, SSP5–8.5 for 2015–2100), we identify high‐performing models (e.g., CNRM‐CM6‐1‐HR, MIROC‐ES2L) and highlight underperforming models (e.g., CanESM5‐CanOE). Using the novel HC‐GDM ranking, an optimal subset of 11 GCMs is selected, ensuring robust ensemble construction. Ensemble experiments demonstrate that constrained least squares ensembles (CLSE) outperform equal‐weighted, machine learning and probabilistic methods by reducing bias and effectively managing outliers. For drought characterisation, K‐component Gaussian mixture modelling (K‐CGMM) captures extremes more accurately than traditional univariate distributions. Drought assessment using the proposed IW‐GSPI reveals stable conditions under SSP1–2.6, intensification under SSP2–4.5, and persistent multi‐year severe droughts under SSP5–8.5, further supported by Markov chain analysis. In summation, IIREDA advances methodological rigour in climate risk assessment, providing redundancy‐resilient, probabilistic drought projections to inform mitigation and adaptation strategies.

Facile fabrication of NiO/MnO2/CuO nanocomposite as robust electrode material for electrochemical water splitting - Atif Nazir; Chanda Sehar; Muhammad Fahad Saeed; Areej Fatima; Wael dheaa Kadhim; Zainab Ahmed Abass; Imran Shakir; Aboud Ahmed Awadh Bahajjaj; Muhammad Ali Khan; S. Shah (Fuel, 2026)

Retraction Note: Novel acetamide derivatives of 2-aminobenzimidazole prevent inflammatory arthritis in rats via suppression of pro-inflammatory mediators - Aymun Madni Zubair; Muhammad Nasir Hayat Malik; Waqas Younis; Muhammad Atif Hayat Malik; Shah Jahan; Ishtiaq Ahmed; Alamgeer Yuchi; Muhammad Naveed Mushtaq; Romeeza Tahir; Muhammad Bilal Sarwar; Muhammad Roman; Ayaz Ali Khan; et al. (Inflammopharmacology, 2026)

Investigation of photocatalytic efficiency and antimicrobial activity via Mn doped SnO2 using an eco-friendly green synthesis method - Laraib Bibi; Tahir Iqbal; Mariam Seemab; Sumera Afsheen; I.M. Ashraf; Faiza Saeed; Atif Mossad Ali; Muhammad Yousaf; M.A. Sayed (Journal of Environmental Chemical Engineering, 2026)

Antibacterial Activity of Anthraquinones Isolated from Reynoutria Japonica Against Staphylococcus aureus: An in Silico and In Vitro Approach - Iqra Anam Khawaja; Sajid Ali; Muhammad Faheem; Syed Babar Jamal; Adnan Haider; Falak Niaz; Mi-Jeong Ahn; Mutiullah Khattak; Atif Ali Khan Khalil (Journal of Pharmaceutical Innovation, 2026)

Phytochemical Profiling and Evaluation of the Anti-inflammatory and Antinociceptive Effects of Lilium polyphyllum Bulb Using In Silico, In Vitro and In Vivo Models - Haider Ali; Shafiq Ur Rahman; Umair Sayad; Atif Ali Khan Khalil; Muzaffar Abbas; Muhammad Shahid (Journal of Pharmaceutical Innovation, 2026)

Natural products in medicinal chemistry: targeting inflammatory pathways with plant-derived compounds - Adnan Amin; Muhammad Saeed Akhtar; Atif Ali Khan Khalil; Sajid Ali; Wajid Zaman (Medicinal Chemistry Research, 2026)

The potential influence of food additives and contaminants on the gut microbiota: A comprehensive review - Sana Ullah; Sher Ali; Muhammad Atif; Muhib Ullah; Ghulam Nabi; Lucas Gabriel Dionisio Freire; Eliana Setsuko Kamimura; Amir Sasan Mozaffari Nejad; Carlos Augusto Fernandes de Oliveira (Food and Chemical Toxicology, 2025)

Halotolerant Bacillus Aryabhattai Strain PM34 Mitigates Salinity Stress and Enhances the Physiology and Growth of Maize - Muhammad Atif Azeem; Salman Khan; Fawad Ali; Sajjad Ahmad; Gul Rahim; Muhammad Iftikhar; Majid Iqbal; Rawa Saad Aljaloud; Khaloud Mohammed Alarjani; Hassan Javed Chaudhary (Journal of Plant Growth Regulation, 2025)

Exploring the therapeutic potential of Nasturtium microphyllum (Boenn.) Rchb.: a combined in-vitro, in-vivo and in-silico approach - Rabia Khan; Muhammad Musa; Syed Mubassir Shah; Hussan Ara Begum; Alaa S. Alhegaili; Sajid Hussain; Atif Ali Khan Khalil; Sajid Ali (Inflammopharmacology, 2025)

Recent advances in conducting polymers for hybrid solar-driven evaporation systems: Fundamentals, innovations, and applications - Bushra Shakoor; Muhammad Sultan Irshad; Uzma Ghazanfar; Humaira Razzaq; Naila Arshad; Ghazala Maqsood; Iftikhar Ahmed; Muhammad Atif Ali; Muhammad Sohail Asghar; Irshad Hussain; Tao Mei; Tran Vinh Dieu; et al. (Chemical Engineering Journal, 2025)

NiMn-LDH/polypyrrole photothermal structures for interfacial solar steam generation - Ghazala Maqsood; Muhammad Sohail Asghar; Bushra Shakoor; Muneerah Alomar; Muhammad Atif Ali; Yi E; Tao Mei; Muhammad Sultan Irshad; Xianbao Wang (Chemical Engineering Journal, 2025)

Bacillus Inoculation Along with Biogas Slurry Mitigates Nickel Stress in Raphanus Sativus by Regulating Ni Accumulation and the Antioxidant Defense System - Iftikhar Ahmad; Shehzad Mehmood; Muhammad Atif Muneer; Aftab Jamal; Amjad Farooq; Muhammad Farhan Saeed; Qasim Ali; Umar Daraz; Nabil Touzout; Adil Mihoub; Jun Zhou (Water, Air, & Soil Pollution, 2025)

An effective bi-functional electrocatalyst for electrochemical water splitting using NiCo2O4 nanoparticles decorated with Polypyrrole nanocomposite - Khadija-Tul-Kubra; Faiqa Noreen; Ali Junaid; Atif Nazir; Sehrish Arshad; Komal Bibi; Ayesha Batool; Aleeza Sattar; Aboud Ahmed Awadh Bahajjaj; Sohail Ahmad; Muhammad Shuaib Khand; Syed Imran Abbas Shah (Fuel, 2025)

Comprehensive Molecular Profiling of AcrAB-TolC Efflux Pump Genes in Salmonella typhi Isolates from Typhoid Infected Patients - Muhammad; Sadiq Azam; Noor Rehman; Alaa S. Alhegaili; Ibrar Khan; Aakash Ahmad; Atif Ali Khan Khalil; Sajid Ali (Current Microbiology, 2025)

Functionalized carbon nanotubes interconnected with metal-organic frameworks for in-situ solar-driven evaporation and salt recovery from seawater - Muhammad Sohail Asghar; Muhammad Sultan Irshad; Naila Arshad; Maryam Al Huwayz; Muneerah Alomar; Ghazala Maqsood; Muhammad Atif Ali; Uzma Ghanzanfar; Muhammad Sabir; Jinhua Li; Van-Duong Dao; Nang Xuan Ho; et al. (Water Research, 2025)

Importance of an Oncology Interest Group in Medical School: Experience from a Developing Country - Hammad Atif Irshad; Abdul Rehman; Muhammad Ali Akbar Khan; Dahir Ashfaq; Munira Moosajee (Journal of Cancer Education, 2025)

Quantitative analysis of pathogenesis-related protein expression in Gossypium hirsutum L. to elicitor-induced resistance against cotton leaf curl disease and predicted in-silico protein-protein interactions - Muhammad Fahad Khan; Syed Atif Hasan Naqvi; Adnan Iqbal; Seth Alan Steichen; Amjad Ali; Rana Muhammad Amir Gulzar; Judith K. Brown; Ummad Ud Din Umar (Physiological and Molecular Plant Pathology, 2025)

Interactive effects of soil moisture and temperature on chromium-induced microbial and enzymatic stress - Idrees Haider; Muhammad Arif Ali; Muhammad Sanaullah; Muhammad Taimoor Shakeel; Syed Atif Hasan Naqvi; Muhammad Akmal; Muhammad Abid Ali Khan; Muhammad Umer Iqbal; Niaz Ahmad; Mahmoud Moustafa; Mohammed O. Alshaharni; Uthman Algopishi (World Journal of Microbiology and Biotechnology, 2025)

Status and prospects of omics in lentil: understanding mechanisms and impact on stress breeding under changing climate - Fawad Ali; Yiren Zhao; Arif Ali; Mian Abdur Rehman Arif; Obaid Ullah Shah; Muhammad Atif Azeem; Li Liao; Zhiyong Wang (Journal of Plant Biochemistry and Biotechnology, 2025)

Spatiotemporal pattern of climatic water balance over Balochistan, Pakistan for the period 1961–2016 - Muhammad Qasim; Kamal Ahmed; Aman Jan; Najeebullah Khan; Atif Muhammad Ali (Theoretical and Applied Climatology, 2025)

In Silico Comparison of WRKY Transcription Factors in Wild and Cultivated Soybean and Their Co-expression Network Arbitrating Disease Resistance - Muhammad Amjad Nawaz; Hafiz Kashif Khalil; Farrukh Azeem; Muhammad Amjad Ali; Igor Eduardovich Pamirsky; Kirill S. Golokhvast; Seung Hwan Yang; Rana Muhammad Atif; Gyuhwa Chung (Biochemical Genetics, 2025)

Effect of Arsenic Exposure on AS3MT Protein Levels in Serum of Type 2 Diabetic Patients Compared to Non-diabetics - Saima Shokat; Riffat Iqbal; Muhammad Ahmed Ali; Atif Yaqub; Shaista Aslam; Samreen Riaz (Biological Trace Element Research, 2024)

Potential of iron oxide-modified biochar in simultaneous mitigation of lead and nickel toxicity in wheat (Triticum aestivum L.) - Tufail Shah; Muhammad Kashif Irshad; Wasim Javed; Mahshab Sheraz; Atif Muhmood; Ali Noman; Maryam M. Alomran; Sang Soo Lee; Jianying Shang (South African Journal of Botany, 2024)

Harmonizing traditional and biotechnological approaches to engineer crop microbiomes: Enhancing resilience optimization - Muhammad Siddique Afridi; Abdul salam; Sher Ali; Sumaira; Willian César Terra; Baber Ali; Muhammad Atif Muneer; Gustavo Santoyo (Biocatalysis and Agricultural Biotechnology, 2024)

Deciphering fungicide resistance in Phytophthora: mechanisms, prevalence, and sustainable management approaches - Syed Atif Hasan Naqvi; Muhammad Farhan; Muhammad Ahmad; Rafia Kiran; Noor Fatima; Muhammad Shahbaz; Muhammad Akram; Jaya Seelan Sathiya Seelan; Amjad Ali; Salman Ahmad (World Journal of Microbiology and Biotechnology, 2024)

Spatio-temporal remote sensing evaluation of drought impact on vegetation dynamics in Balochistan, Pakistan - Atif Muhammad Ali; Haishen Lü; Yonghua Zhu; Kamal Ahmed; Muhammad Farhan; Muhammad Qasim (Theoretical and Applied Climatology, 2024)

Retraction Note: Novel mannich-based derivative of 2-mercaptobenzimidazole (AK7): a new candidate for the treatment of inflammatory arthritis owing to its NF-κB1 inhibitory potential - Gagun Kamran; Hafiz Amir Ali Kharl; Muhammad Nasir Hayat Malik; Waqas Younis; Humaira Nadeem; Aymun Madni Zubair; Muhammad Atif Hayat Malik; Shah Jahan; Ishtiaq Ahmed; Ramla Shabbir; Asma Akram; Irfan Anjum; et al. (Naunyn-Schmiedeberg's Archives of Pharmacology, 2024)

Facilitated transport of ferrihydrite with phosphate under saturated flow conditions - Tufail Shah; Kang Zhao; Ai Chen; Atif Muhmood; Syed Atizaz Ali Shah; Muhammad Kashif Irshad; Yuji Arai; Jianying Shang (Journal of Contaminant Hydrology, 2024)

Extremophiles and their enzymatic diversity and biotechnological potential - Fatima Atif; Nida Maqsood; Wajeeha Ali; Wajid Ali; Muhammad Irfan (Systems Microbiology and Biomanufacturing, 2024)

Inhibitory potential of Syzygium aromaticum against Fusarium oxysporum f. sp. lycopersici: In-vitro analysis and molecular docking studies - Muhammad Atif; Tehmina Anjum; Ahmad Ali Shahid; Ahmad Hassan; Waheed Akram (South African Journal of Botany, 2024)

Genomic insights into local adaptation of upland cotton in China and Pakistan - Zegang Han; Zhanfeng Si; Mehboob-ur Rahman; Lu He; Yiqian Li; Ali Qaiser Khan; Yun Mao; Sana Zulfiqar; Shumila Ishfaq; Muhammad Mohsan; Muhammad Atif Iqbal; Saba Zafar; et al. (Theoretical and Applied Genetics, 2024)

Appraisal of the health hazards associated with the ingestion of vegetables contaminated with potentially toxic elements - Ali Afzal; Atif Muhmood; Syed Ayyaz Javed; Arslan Nazarat; Muhammad Rashid; Asrar Hussain Shah; Farhana Siddique (Arabian Journal of Geosciences, 2024)

Unveiling Intricacies of Mango Malformation Dynamics Caused by Fusarium solani Through Extensive Field Surveys and Laboratory, Epidemiology, and Model-Based Insights - Abdurrehman; Talha Mansoor; Muhammad Nasir Subhani; Muhammad Tariq Malik; Ammarah Hasnain; Aqleem Abbas; Abdulwahed Fahad Alrefaei; Haider Ali; Muhammad Zeeshan Hassan; Syed Atif Hasan Naqvi (Applied Fruit Science, 2024)

CRISPR/Cas9-based genome editing: A revolutionary approach for crop improvement and global food security - Ghulam Muha-Ud-Din; Faizan Ali; Akhtar Hameed; Syed Atif Hasan Naqvi; Mir Muhammad Nizamani; Muhammad Jabran; Sohaib Sarfraz; Wang Yong (Physiological and Molecular Plant Pathology, 2024)

Assessing coastal bathymetry and climate change impacts on coastal ecosystems using Landsat 8 and Sentinel-2 satellite imagery - Kasypi Mokhtar; Lai Fatt Chuah; Mohd Azhafiz Abdullah; Olakunle Oloruntobi; Siti Marsila Mhd Ruslan; Gadah Albasher; Atif Ali; Muhammad Saeed Akhtar (Environmental Research, 2023)

Enhancing coastal ecosystem resilience: Investigating the interplay between safety criteria and ferry employee's perceptions to address climate change impacts - Muhammad Azizol Azmi; Kasypi Mokhtar; Noor Apandi Osnin; Suzanna Razali Chan; Gadah Albasher; Atif Ali; Alam Nawaz; Olakunle Oloruntobi; Lai Fatt Chuah (Environmental Research, 2023)

Unlocking the secrets of soil microbes: How decades-long contamination and heavy metals accumulation from sewage water and industrial effluents shape soil biological health - Idrees Haider; Muhammad Arif Ali; Muhammad Sanaullah; Niaz Ahmed; Sajjad Hussain; Muhammad Taimoor Shakeel; Syed Atif Hasan Naqvi; Javeed Shabbir Dar; Mahmoud Moustafa; Mohammed O. Alshaharni (Chemosphere, 2023)

Risk assessment of toxic and hazardous metals in paddy agroecosystem by biochar-for bio-membrane applications - Muhammad Kashif Irshad; Sihang Zhu; Wasim Javed; Jong Cheol Lee; Abid Mahmood; Sang Soo Lee; Shang Jianying; Gadah Albasher; Atif Ali (Chemosphere, 2023)

Effect of green synthesized cerium oxide nanoparticles on fungal disease of wheat plants: A field study - Modhi O. Alotaibi; Nahaa M. Alotaibi; Adel M. Ghoneim; Noor ul Ain; Muhammad Atif Irshad; Rab Nawaz; Tahir Abbas; Amjad Abbas; Muhammad Rizwan; Shafaqat Ali (Chemosphere, 2023)

Novel sol–gel synthesis of Mo-doped ZnO-NPs for photo-catalytic waste water treatment using the RhB dye as a model pollutant - Muhammad Sohaib; Tahir Iqbal; Sumera Afsheen; M. B. Tahir; Arslan Masood; Muhammad Rafique; K. N. Riaz; M. A. Sayed; A. F. Abd El-Rehim; Atif Mossad Ali (Environment, Development and Sustainability, 2023)

Preparation and characterization of single perovskite microplates and its sunlight assisted photodecolorization activity, validated by response surface methodology - Arif Nawaz; Irum Naz; Muhammad Atif; Adnan Khan; Nisar Ali (Chemosphere, 2023)

Transcriptomic analysis of Cucumis sativus uncovers putative genes related to hormone signaling under low temperature (LT) and high humidity (HH) stress - Bakht Amin; Muhammad Jawaad Atif; Yupeng Pan; Shabir A. Rather; Muhammad Ali; Shuju Li; Zhihui Cheng (Plant Science, 2023)

Effect of titanium dioxide nanoparticles and co-composted biochar on growth and Cd uptake by wheat plants: A field study - Fu Chen; Yuhang Li; Muhammad Atif Irshad; Afzal Hussain; Rab Nawaz; Muhammad Farooq Qayyum; Jing Ma; Muhammad Zia-ur-Rehman; Muhammad Rizwan; Shafaqat Ali (Environmental Research, 2023)

Solar light driven degradation of textile dye contaminants for wastewater treatment – studies of novel polycationic selenide photocatalyst and process optimization by response surface methodology desirability factor - Arif Nawaz; Muhammad Atif; Adnan Khan; Mohsin Siddique; Nisar Ali; Falak Naz; Muhammad Bilal; Tak H. Kim; Malwina Momotko; Hameed Ul Haq; Grzegorz Boczkaj (Chemosphere, 2023)

“Retraction notice to Carveol ameliorates mercury-induced oxidative stress, neuroinflammation, and neurodegeneration in a mouse brain” NeuroToxicology 92 (2022) 212–226 - Abdullah Alattar; Arooj Mohsin Alvi; Sajid Rashid; Nadia Hussain; Mehreen Gul; Muhammad Ikram; Atif Ali Khan Khalil; Reem Alshaman; Fawad Ali Shah; Shupeng Li; Jingbo Li (NeuroToxicology, 2023)

Co-opted directors and greenhouse gas emissions: Does ESG compensation matter? - Ammar Ali Gull; Aitzaz Ahsan Alias Sarang; Irfan Haider Shakri; Muhammad Atif (Journal of Cleaner Production, 2023)

Synthesis, characterization and antifungal potential of titanium dioxide nanoparticles against fungal disease (Ustilago tritici) of wheat (Triticum aestivum L.) - Nadiyah M. Alabdallah; Muhammad Atif Irshad; Muhammad Rizwan; Rab Nawaz; Aqil Inam; Muhammad Mohsin; Iram Khurshid; Hesham F. Alharby; Atif A. Bamagoos; Shafaqat Ali (Environmental Research, 2023)

Effects of silicon nanoparticles and conventional Si amendments on growth and nutrient accumulation by maize (Zea mays L.) grown in saline-sodic soil - Ali Rizwan; Muhammad Zia-ur-Rehman; Muhammad Rizwan; Muhammad Usman; Sidra Anayatullah; Areej; Hesham F. Alharby; Atif A. Bamagoos; Basmah M. Alharbi; Shafaqat Ali (Environmental Research, 2023)

Exploration of plant growth promoting traits and regulatory mechanisms of Bacillus anthracis PM21 in enhancing salt stress tolerance in maize - Muhammad Atif Azeem; Fawad Ali; Abid Ullah; Mahmood Iqbal; Kishwar Ali; Dunia A. Al Farraj; Mohamed S. Elshikh; Qirat Naz; Muhammad Farooq Hussain Munis; Hassan Javed Chaudhary (Environmental Science and Pollution Research, 2023)

A review on covalent organic frameworks as adsorbents for organic pollutants - Awais Ali Aslam; Adnan Irshad; Muhammad Shahid Nazir; Muhammad Atif (Journal of Cleaner Production, 2023)

RETRACTED ARTICLE: Novel mannich-based derivative of 2-mercaptobenzimidazole (AK7): a new candidate for the treatment of inflammatory arthritis owing to its NF-κB1 inhibitory potential - Gagun Kamran; Hafiz Amir Ali Kharl; Muhammad Nasir Hayat Malik; Waqas Younis; Humaira Nadeem; Aymun Madni Zubair; Muhammad Atif Hayat Malik; Shah Jahan; Ishtiaq Ahmed; Ramla Shabbir; Asma Akram; Irfan Anjum; et al. (Naunyn-Schmiedeberg's Archives of Pharmacology, 2023)

Effect of farmyard manure, elemental sulphur and EDTA on growth and phytoextraction of cadmium by spider plants (Chlorophytum comosum L.) under Cd stress - Muhammad Zia-ur-Rehman; Arisha Mubsher; Muhammad Rizwan; Muhammad Usman; Muhammad Jafir; Muhammad Umair; Hesham F. Alharby; Atif A. Bamagoos; Rahma Alshamrani; Shafaqat Ali (Chemosphere, 2023)

Biochemical and Physiological Responses of Cucumis sativus Cultivars to Different Combinations of Low-Temperature and High Humidity - Bakht Amin; Muhammad Jawaad Atif; Huanwen Meng; Muhammad Imran Ghani; Muhammad Ali; Xiao Wang; Yuanyuan Ding; Xiuju Li; Zhihui Cheng (Journal of Plant Growth Regulation, 2023)

A quantitative assessment of pollution from potentially toxic elements in groundwater and the accompanying health risks - Atif Muhmood; Abdul Majeed; Abid Niaz; Asrar Hussain Shah; Ali Afzal; Khaliq ur Rehman Arshad; Muhammad Rashid; Arslan Nazarat (Arabian Journal of Geosciences, 2022)

Diversified crop rotation improves continuous monocropping eggplant production by altering the soil microbial community and biochemical properties - Muhammad Imran Ghani; Ahmad Ali; Muhammad Jawaad Atif; Shamina Imran Pathan; Giacomo Pietramellara; Muhammad Ali; Bakht Amin; Zhihui Cheng (Plant and Soil, 2022)

Adenosine A2A receptor as a potential target for improving cancer immunotherapy - Muhammad Atif; Abdullah Alsrhani; Farrah Naz; Muhammad Ikram Ullah; Ayman Ali Mohammed Alameen; Muhammad Imran; Hasan Ejaz (Molecular Biology Reports, 2022)

A novel lens of stock market capitalization and environmental degradation - Aamir Azeem; Muhammad Akram Naseem; Naveed Ul Hassan; Ijaz Butt; Muhammad Toseef Aslam; Shahid Ali; Atif khan Jadoon (Environmental Science and Pollution Research, 2022)

RETRACTED ARTICLE: Novel acetamide derivatives of 2-aminobenzimidazole prevent inflammatory arthritis in rats via suppression of pro-inflammatory mediators - Aymun Madni Zubair; Muhammad Nasir Hayat Malik; Waqas Younis; Muhammad Atif Hayat Malik; Shah Jahan; Ishtiaq Ahmed; Alamgeer Yuchi; Muhammad Naveed Mushtaq; Romeeza Tahir; Muhammad Bilal Sarwar; Muhammad Roman; Ayaz Ali Khan; et al. (Inflammopharmacology, 2022)

Assessing the prioritization of barriers toward green innovation: small and medium enterprises Nexus - Fengsheng Chien; Hafiz Waqas Kamran; Muhammad Atif Nawaz; Nguyen Ngoc Thach; Pham Dinh Long; Zulfiqar Ali Baloch (Environment, Development and Sustainability, 2022)

A multi-perspective assessment approach of renewable energy production: policy perspective analysis - Zulfiqar Ali Baloch; Qingmei Tan; Hafiz Waqas Kamran; Muhammad Atif Nawaz; Gadah Albashar; Javaria Hameed (Environment, Development and Sustainability, 2022)

Genome-wide identification and characterization of a plant-specific Dof transcription factor gene family in olive (Olea europaea) and its comparison with Arabidopsis - Mariyam; Muhammad Shafiq; Muhammad Haseeb; Rana Muhammad Atif; Syed Agha Armaghan Asad Abbas Naqvi; Numan Ali; Muhammad Arshad Javed; Fizza Gillani; Muhammad Saleem Haider (Horticulture, Environment, and Biotechnology, 2021)

Historical trends in crop water demand over semiarid region of Syria - Rajab Homsi; Shamsuddin Shahid; Zafar Iqbal; Atif Muhammad Ali; Ghaith Falah Ziarh (Theoretical and Applied Climatology, 2021)

Deciphering distinct biological control and growth promoting potential of multi-stress tolerant Bacillus subtilis PM32 for potato stem canker - Shehzad Mehmood; Muhammad Atif Muneer; Muhammad Tahir; Muhammad Tariq Javed; Tariq Mahmood; Muhammad Siddique Afridi; Najeeba Paree Pakar; Hina Ali Abbasi; Muhammad Farooq Hussain Munis; Hassan Javed Chaudhary (Physiology and Molecular Biology of Plants, 2021)

Geological and petrographic investigations of the Miocene Molasse deposits in Sub-Himalayas, District Sudhnati, Pakistan - Asim Javed; Ali Wahid; Muhammad Saleem Mughal; Muhammad Sabir Khan; Raja Saad Qammar; Syed Haroon Ali; Numair Ahmad Siddiqui; Muhammad Atif Iqbal (Arabian Journal of Geosciences, 2021)

The impacts of land use/land cover changes on the supply-demand budget of urban ecosystem services - Syed Atif Bokhari; Zafeer Saqib; Amjad Ali; Arif Mahmud; Nadia Akhtar; Ambrina Kanwal; Muhammad Zaman ul Haq (Arabian Journal of Geosciences, 2021)

In vitro differentiation effect of CCL4-induced liver injured mice serum on bone marrow-derived mesenchymal stem cells toward hepatocytes like cells - Sulaiman Shams; Nazia Imran; Sahib Gul Afridi; Muhammad Ayaz; Atif Ali Khan Khalil; Abdul Nasir (Cell and Tissue Banking, 2021)

Determinants of farmers’ adaptation to climate change in rain-fed agriculture of Pakistan - Sarah Amir; Zafeer Saqib; Muhammad Irfan Khan; Akhter Ali; Muhammad Azeem Khan; Syed Atif Bokhari; Zaman-ul-Haq (Arabian Journal of Geosciences, 2020)

HPLC-UV characterization, anticholinesterase, and free radical-scavenging activities of Rosa moschata Herrm. leaves and fruits methanolic extracts - Nausheen Nazir; Atif Ali Khan Khalil; Mohammad Nisar; Muhammad Zahoor; Sajjad Ahmad (Brazilian Journal of Botany, 2020)

The impact of airborne pollution and exposure to solar ultraviolet radiation on skin: mechanistic and physiological insight - Atif Ali; Hira Khan; Raheem Bahadar; Asma Riaz; Muhammad Hassham Hassan Bin Asad (Environmental Science and Pollution Research, 2020)

Lipids as biomarkers of brain disorders - Ghulam Hussain; Haseeb Anwar; Azhar Rasul; Ali Imran; Muhammad Qasim; Shamaila Zafar; Muhammad Imran; Syed Kashif Shahid Kamran; Nimra Aziz; Aroona Razzaq; Waseem Ahmad; Asghar Shabbir; et al. (Critical Reviews in Food Science and Nutrition, 2020)

Synthesis and Application of Titanium Dioxide Nanoparticles for Removal of Cadmium from Wastewater: Kinetic and Equilibrium Study - Muhammad Atif Irshad; Muhammad Bilal Shakoor; Shafaqat Ali; Rab Nawaz; Muhammad Rizwan (Water, Air, & Soil Pollution, 2019)

Anti-pollution cosmetic-based one-step formation of w/o/w multiple emulsion containing D-biotin for skin protection: fabrication and in vitro and in vivo evaluation - Atif Ali; Sajid Iqbal; Aqsa Ilyas; Hira Khan; Muhammad Hassham Hassan Bin Asad; Nighat Fatima; Naveed Akhtar (Drug Delivery and Translational Research, 2019)

Genome-wide identification and expression analyses of WRKY transcription factor family members from chickpea (Cicer arietinum L.) reveal their role in abiotic stress-responses - Muhammad Waqas; Muhammad Tehseen Azhar; Iqrar Ahmad Rana; Farrukh Azeem; Muhammad Amjad Ali; Muhammad Amjad Nawaz; Gyuhwa Chung; Rana Muhammad Atif (Genes & Genomics, 2019)

Characterization of Cellulose Synthase A (CESA) Gene Family in Eudicots - Muhammad Amjad Nawaz; Xiao Lin; Ting-Fung Chan; Muhammad Imtiaz; Hafiz Mamoon Rehman; Muhammad Amjad Ali; Faheem Shehzad Baloch; Rana Muhammad Atif; Seung Hwan Yang; Gyuhwa Chung (Biochemical Genetics, 2019)

Effect of foliar-applied iron complexed with lysine on growth and cadmium (Cd) uptake in rice under Cd stress - Arooj Bashir; Muhammad Rizwan; Shafaqat Ali; Muhammad Zia ur Rehman; Wajid Ishaque; Muhammad Atif Riaz; Arosha Maqbool (Environmental Science and Pollution Research, 2018)

Genome-Wide Analysis of Potassium Transport-Related Genes in Chickpea (Cicer arietinum L.) and Their Role in Abiotic Stress Responses - Farrukh Azeem; Bilal Ahmad; Rana Muhammad Atif; Muhammad Amjad Ali; Habibullah Nadeem; Sabir Hussain; Hamid Manzoor; Muhammad Azeem; Muhammad Afzal (Plant Molecular Biology Reporter, 2018)

Pre-planting exogenous application of gibberellic acid influences sprouting, vegetative growth, flowering, and subsequent bulb characteristics of ‘Ad-Rem’ tulip - Fahad Ramzan; Adnan Younis; Atif Riaz; Sajid Ali; Muhammad Irfan Siddique; Ki-Byung Lim (Horticulture, Environment, and Biotechnology, 2014)

Microsatellite analysis of Rosa damascena from Pakistan and Iran - Amjad Farooq; Mahnaz Kiani; Muhammad Aslam Khan; Atif Riaz; Asif Ali Khan; Natalie Anderson; David H. Byrne (Horticulture, Environment, and Biotechnology, 2013)